Cabaran Peniaga Cina dalam Sektor Penghasilan Makanan di Butterworth, 1900-2000 - Tan Soon Chin (Tanjong Malim, 2021)
Cabaran Peniaga Cina dalam Sektor Penghasilan Makanan di Butterworth, 1900-2000 by Tan Soon Chin